Leptochloa Fusca Cultivation for Utilization of Salt - affected Soil and Water Resources in Cholistan Desert / Cultivo de Leptochloa Fusca para a utilização de solos afetados por sais e recursos hídricos no Deserto de Cholistan - Ahmad, Farooq (Sociedade & Natureza, 2010)
In Cholistan desert, 0.44 million hectares are salt-affected low lying and clayey in nature locally known as "dharsï¿½ï¿½?, where rainwater as well as saline groundwater could be utilized for growing salt grasses like Leptochloa fusca as forage during summer. L. fusca is a promising candidate grass for economic utilization and better management of sodic, high pH, saline soil and saline water resources of Cholistan desert. L. fusca is known to be a versatile, halophytic, primary colonizer, easily propagatable, perennial, nutritive and palatable forage plant species. The grass has the good biomass producing potential and can grow equally well both under upland and submerged saline soil environment.